2020
DOI: 10.1016/j.jdermsci.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The current landscape of psoriasis genetics in 2020

Abstract: Psoriasis is an immune-mediated disease associated with skin and joint inflammation that affects large proportions of populations worldwide. It is a heritable disease: individuals' genetic backgrounds modulate their susceptibility. In genetics, multiple human leukocyte antigen (HLA) genes are most strongly associated with the risk of psoriasis, especially HLA-C*06:02. In the last 10 years, large-scale genome-wide association studies (GWASs) of psoriasis have been conducted in multiple populations, and these ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 51 publications
1
83
0
6
Order By: Relevance
“…(4) Vitamin digestion and absorption pathway was enriched in PsC than in PsA. (5) The major subnetwork among metabolites with differences between PsA and PsC was primarily formed from saturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Vitamin digestion and absorption pathway was enriched in PsC than in PsA. (5) The major subnetwork among metabolites with differences between PsA and PsC was primarily formed from saturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis vulgaris is the most common type of psoriasis, which can cause various complications, such as psoriatic arthritis (PsA), cardiovascular disease, and metabolic syndrome [2,3]. PsA is a severe form of arthritis with joint deformities and damage, present in approximately 30 % of patients with psoriasis [4,5]. The crosstalk between genetic and environmental factors (e.g., diet and lifestyle) is responsible for psoriasis by contributing to immunological abnormalities and epidermal proliferation [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, psoriasis genome-wide association studies (GWAS) have been conducted worldwide, and numbers of genetic loci associated with psoriasis susceptibility have been estimated (Ogawa & Okada, 2020). Previews studies showed that approximately 10% of autoimmune disease-associated SNPs localize to lncRNA genes present in autoimmune disease-associated loci, and SNPs can affect the expression of lncRNAs (Kumar et al, 2013).…”
Section: Control Psoriasismentioning
confidence: 99%
“…Psoriasis is caused by several complex factors, both environmental and genetic, many of which are still not fully understood [4,5]. Nowadays, genetic studies are useful tools to identify potential new targets for psoriasis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, genetic studies are useful tools to identify potential new targets for psoriasis treatment. With advances in single nucleotide polymorphism (SNP) microarray technology and large-scale genome databases, genome-wide association studies (GWAS) have been conducted to study multiple traits and diseases [5]. Molecular genetics studies have identified more than 80 genomic loci involved in about 30% of psoriasis heritability, which show variation associated with risk of disease [6] Like several other multifactorial autoimmune disorders, psoriasis manifests strong associations with HLA, mostly with HLA-C, in particular with the HLA-C*06:02 allele, which was the first risk allele identified for psoriasis, presenting certain differences amongst different races [5,7].…”
Section: Introductionmentioning
confidence: 99%